Did the recommended retail price of tobacco products fall in Australia following the implementation of plain packaging?. (25th February 2015) - Scollo, Michelle; Bayly, Megan; Wakefield, Melanie
Abstract : Objectives: This study aimed to assess the extent of any fall in recommended retail prices (RRPs) of tobacco products sold in Australia following the 2012 implementation of plain packaging. Methods: RRPs published in price lists by the New South Wales Retail Tobacco Traders Association covering the months of November 2011, November 2012 and November 2013 were recorded for all listed brands and pack sizes. Average prices per stick were computed in 2013 dollars for cigarette brands in each of 10 possible pack sizes, for each major tobacco manufacturer, and across market segments. Average prices per gram in Australian dollars adjusted to 2013 prices (AUD2013) were calculated for roll-your-own (RYO) tobacco brands for each major manufacturer. Results: Inflation-adjusted average RRPs per stick in November 2013 were on average 6.4% higher than in November 2011 and 3.4% higher than in November 2012. The average RRP per gram of RYO products in November 2013 was 10.2% and 5.4% higher than in November 2011 and November 2012, respectively. Within cigarette brands, the highest increases in RRP from 2011 to 2013 were seen among mainstream and premium brands (10.0% and 10.1%, respectively) and among packs of 30s (18.3%) and 50s (12.5%). Conclusions: The RRPs of tobacco products were higher in real terms 1 year after Australia's plain packaging legislation was implemented. These increases exceeded increases resulting from Consumer Price Index (CPI) indexation of duty and occurred across all three major manufacturers for both factory made and RYO brands, all three cigarette market segments and all major pack sizes.